Implementation of bela Beli Kulonprogo in Producing Drinking Water in Packaging Kulonprogo District - Ferid Nugroho (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
The Bela Beli Kulon Progo policy is a policy that inspires the enthusiasm and spirit ofKulon Progo Regency residents to improve their welfare. Through the slogan madhepmanggep dandruff banyu banyune dhewe which was originally a concern He KulonProgo see the conditions around him. Why not just to drink the public must consumebottled drinks originating from foreign countries where national companies worktogether with foreign companies to produce bottled drinking water. To prevent thedependence of the community on foreign products related to bottled water, He KulonProgo made a policy related to Bela Beli Kulon Progo with a program to produce bottled water in the My Water brand produced by PDAM Tirta Binangun which is aBUMD owned by the Kulonprogo Regency Government. The consumption of drinkingwater in Packaging in Kulon Progo Regency has recently reached 6 million litters permonth. So the Kulon Progo Regency government wants to take most of the bottleddrinking water market so that the production of drinking water can be met by PDAMTirta Binangun. He felt that this market was very potential to become a place for PDAMTirta Binangun to sell its products.